GOOD FAITH IN THE EXERCISE OF THE NOTARY OFFICE ACCORDING TO THE NOTARY OFFICE ACT IN CASES OF THE CRIMINAL OFFENSE OF DOCUMENT FORGERY - Abdul Herris Rusli, (Proceeding International Conference on Social Sciences, 2026)
A notary is a public official authorized by the state to draw up authentic deeds which possess full evidentiary strength. This position makes the notary an essential part of the legal system in ensuring legal certainty, protection, and order in society. However, this significant responsibility also carries legal risks, one of which is the allegation of document forgery. In practice, forgery cases involving notaries generally arise from the misuse or falsification of documents submitted by the parties. A notary, who relies solely on the data and information provided by the appearers, is often implicated in criminal issues even though they are not directly involved in the act itself. This situation creates legal uncertainty and injustice for the notarial profession. This study aims to analyze the implementation mechanisms and legal protection of the notary’s office in cases of document forgery, as well as to identify the effectiveness and weaknesses of such legal protection. The approach used is normative legal research with a qualitative nature through literature studies, field surveys, and interviews with notaries and related parties. The findings indicate that legal protection for notaries in cases of alleged document forgery has essentially been regulated under the Notary Office Act, particularly Article 66 of the Act. However, its implementation still faces obstacles in the form of unclear and imprecise provisions of the Act in protecting notaries during the criminal process, including investigation, inquiry, prosecution, and trial in court. The results of this research are expected to provide input for improving or adding special articles to the Notary Office Act. Thus, effective legal protection for notaries not only safeguards the continuity of the profession but also supports the creation of a fair legal system and better legal services for society.